Pulmonary Zygomycosis in a Patient with X-CGD (Global Journal of Medical Research, 2024)
Abstract not found
Keywords: chronic granulomatous disease; cgd; immunodeficiency; primary immunodeficiency; zygomycosis; fungal pneumonia